Educating for a systems design approach to complex societal problems - Costa Junior, Jairo da; Diehl, Jan Carel; Secomandi, Fernando (Taylor & Francis, 2018)
Design education has devoted little attention to the topic of societal systems transformation in the context of sustainable development. This paper reports on a master‘s-level course that aims to build the capacity for design engineering students to adopt a Systems Design Approach comprised of the integration of Product-Service System (PSS) and Systems Thinking, in order to develop sustainable energy systems concepts. We identify key factors for skilful performance when designing solutions for complex societal problems. The findings suggest that design approaches grounded in systems thinking are promising for dealing with the increasing complexity of the societal problems which future generations of design professionals are expected to solve. An Open Learning E-Package (OLEP) was offered to support Higher Education Institutions (HEIs) to introduce Product-Services Systems and Distributed Renewable Energy (DRE) models into their design curricula. We argue that capacity building for a systems design approach to complex societal problems, such as those faced in low-income energy markets, can support future generations of design engineers to take an active role in the development and widespread implementation of sustainable energy systems.